Identification of traditional science-based games to improve early childhood development in Central Lombok District - Baik Nilawati Astini; Ika Rachmayani; Nurhasanah Nurhasanah; Ni Luh Tania Putri Wijaya (Jurnal Pijar Mipa, 2023)
Giving educational stimulation in early childhood can be given through games. Traditional science-based games make an important contribution to supporting children's development. This study aimed to identify traditional games in Central Lombok Regency that can be played in early childhood and how to play traditional games to improve children's development. This research is survey research conducted at Central Lombok Regency. This research uses observation data collection methods, interviews, and documentation. The subjects of this study were six community leaders or cultural leaders and five teachers. Data analysis used descriptive qualitative analysis. The results showed that there were 28 identified traditional games. After being reviewed and verified based on the criteria for tools and materials used: playground, gender, age of players, number of players, and how to play, 23 traditional games were obtained:  fort, bekel, ciwe, cepun, do mi gift, merchandise, long dragon snakes, marbles, playing rope, pese-pese'an, temeong-meong, gobak sodor, trumpets, cingkaleng, manuk brackets, splashing, temong-meong, school stones, playing moon, cupring, segem, playing war and coffee. Traditional games use tools, do not use tools, and use poetry/songs. How to play traditional games each game has steps similar to each others. Based on these criteria, traditional games can indirectly improve child development such as cognitive, language, social-emotional, religious and moral values, physical-motor, and artistic.